XX Century Queen of Imereti - Nestan Kveidze - Khatchapuridze, Ia; Khatchapuridze, Lola (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
Nestan Kveidze - a teacher, scientist, actor, poet, writer, journalist, queen ofImereti... played more than 40 roles, both main and episodic. She approached bothtypes of roles equally, holding the honorable place both on the stage and in life.“Stepmother of Samanishvili“, “Mayakovski had such kind of start”, Pilgrim“, “MyKutaisi“, “Return of naughty“ - these are the films, in which she created memorableroles and that’s how she stayed in the history of Georgian film. She used to talk to theaudience from the stage, from the screen, sometimes with poems, stories, articles,essays, miniatures, graphics... published several poetic selections. She dreamed aboutcollecting her own works published in 52 books. This dream came true with the helpof kind people to whom she was very grateful. Fancy dressed and dreamer, she used to walk in the streets of her city, foreveryoung colorite lit up with the colors of spring and it was clear that Kutaisi was in joyas Nastan Kveidze was walking in its streets.